An approximate graphic method for the determination of the resources requirements in construction industry - Chu, Lee-how; Wireland, Martin; Jearkjirm, Vithool; Ping Kunawatsatit; Government of the Republic of China (Bangkok : Asian Institute of Technology, 1981)
Resources leveling problems in construction industry need a lot of computational effort and preparation. The reliability of the methods available in leveling of resources is always questionable. The frequent changes in time schedules of the projects and the fluctuation of the available resources further, complicate the problem of leveling of resources, A simplified graphical method for resource leveling is discussed in this study. It is based on the concept of the critical path method, resource progress chart and line of balance, Although this graphic method merely yields approximate daily peak resources requirements, it gives a good first estimate for the contractor manager. A five unit housing project in Bangkok is used to illustrate the performance of the model. Results of this study have indicated that this graphical solution can satisfy the maximum peak daily resource requirements in this particular project.
Thesis (M.Eng.) - Asian Institute of Technology, 1981
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Engineering and Technology
Keywords: Network analysis (Planning); Construction equipment